2017
DOI: 10.4093/dmj.2017.41.4.316
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Improved Glycemic Control by Direct-Acting Antiviral Agent Treatment in Egyptian Type 2 Diabetes Mellitus Patients with Chronic Hepatitis C Genotype 4

Abstract: BackgroundThe association of chronic hepatitis C virus (HCV) infection with type 2 diabetes mellitus (T2DM) was first reported in 1994. Little is known about the effect of direct-acting antiviral agents (DAAs) on glycemic control in T2DM patients. The aim of the present study was to evaluate the factors associated with improved glycemic control (IGC) by DAA treatment in Egyptian T2DM patients with chronic HCV genotype 4 infection.MethodsThis study included 460 T2DM patients with chronic HCV genotype 4 infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 19 publications
(20 reference statements)
6
49
0
1
Order By: Relevance
“…SVR induced a significant improvement in glycemic control, despite a significant weight gain and in 20.7% of SVR patients caused in a reduction or discontinuation of antidiabetic therapy [10] Similar data have been reported in a large Egyptian study comprising HCV genotype 4-infected patients treated with DAAs [11]. Patients with improved glycemic control needed a reduction in antidiabetic drugs and insulin dose; the family history of diabetes, the presence of Child B cirrhosis, and the duration of diabetes were associated with non-improvement in glycemic control.…”
supporting
confidence: 61%
“…SVR induced a significant improvement in glycemic control, despite a significant weight gain and in 20.7% of SVR patients caused in a reduction or discontinuation of antidiabetic therapy [10] Similar data have been reported in a large Egyptian study comprising HCV genotype 4-infected patients treated with DAAs [11]. Patients with improved glycemic control needed a reduction in antidiabetic drugs and insulin dose; the family history of diabetes, the presence of Child B cirrhosis, and the duration of diabetes were associated with non-improvement in glycemic control.…”
supporting
confidence: 61%
“…Finally, as this study was performed before widespread access to direct‐acting anti‐viral (DAA) treatments, the overall rate of SVR was low (17.4%). Several studies have shown that HCV clearance by DAA treatments improves IR in patients with mild liver fibrosis but not in patients with advanced liver fibrosis . Therefore, prospective studies should be conducted to assess the impact of early treatment of HCV infection, and of high rates of SVR with DAA treatments, on the occurrence of DM …”
Section: Discussionmentioning
confidence: 99%
“…of patients had to decrease the dose of antidiabetic treatment because of better glycaemic control. 163 In addition, the improvement of insulin resistance is also observed in patients achieving SVR.…”
Section: Chroni C Hepatitis Vir Al Infec Ti On With In Sulin Re S Imentioning
confidence: 99%
“…Additionally, for patients with T2DM, SVR leads to better glycaemic control at 12‐week post‐treatment than before DAA treatment is commenced . Dawood et al further indicated that 26.7% of patients had to decrease the dose of antidiabetic treatment because of better glycaemic control . In addition, the improvement of insulin resistance is also observed in patients achieving SVR.…”
Section: Chronic Hepatitis Viral Infection With Insulin Resistance Anmentioning
confidence: 99%